Section A: The axe of the house Section B: ‘Entangled in biographical circumstances’ - Askew, Claire Louise (The University of Edinburgh, 2014)
The axe of the house is a collection of poetry written and collated over three and a half years. The vast majority of the poems are about women: these are women’s voices usually recounting specifically female experiences. Many of these female poems were informed by the confessional mode, as appropriated and transmuted by the contemporary women writers I read and studied. The collection begins with confessions of my own in poems like “Anne Askew’s ashes” and “Jean,” and then moves on to include love poems like “Prayer” and “Gulls,” which are also at least partially autobiographical. Also confessional, but not autobiographical, are the poems at the centre of this collection. These are poems in which women from various different walks of life speak about their inner lives. Some of these women, like the speakers of “Hate mail” and “Silver Ghost,” are my own creation, while others, like “Mrs Rochester,” are borrowed from elsewhere. These poems examine intimate relationships from various angles: marriages, one night stands and vicious rivalries are all explored via a first person narrative. Body image is also a common theme. There are a few poems which are more overtly political, delivering feminist messages about the ways patriarchal society portrays and often ostracises women. “Harpies,” for example, looks at women who are seen to have no sexual worth, while “The picture in your mind when you speak of whores” concerns women whose only perceived worth is sexual, dismissing the various marginalising stereotypes that exist around sex workers. The collection moves farthest away from its examination of the female experience in the poems towards the end. However, these poems form a travelogue in which privilege of various kinds is examined and critiqued. Poems like “Witch” and “Belongings” are still concerned with the lives of women, while “Big heat” uses a female narrator to examine the more recognised privileges of wealth and mobility. These ideas recur in poems like “Barcelona diptych” and “Highway: Skagit County, WA,” but the poems that round off the collection are also attempts to capture a sense of place and space. Throughout this work, there are poems that are particularly interested in liminal space: several of the poems in the collection, including “Poltergeistrix” and “The women” look at the hours and days immediately after death. The space between travel destinations is also liminal, and these final poems attempt to make sense of it – finally succeeding with “Hydra,” which delivers a sense of acceptance and advocates living ‘in the moment’. The critical section, “Entangled in biographical circumstances,” looks afresh at the female confessional poem, most commonly associated with Sylvia Plath, Anne Sexton and Adrienne Rich. With reference to the works of these literary foremothers, I focus on the ways in which a new generation of women poets has been inspired to adopt this mode. As well as noting the often hostile response of male critics to confessional work by female writers, I examine the very different ways in which Sharon Olds, Sapphire and Liz Lochhead work in the confessional tradition to produce poetry that speaks candidly about the inner lives of women. I also discuss the ways in which the work of these three poets has influenced and shaped my own poetry.
Keywords: poetry; creative writing; feminism; women's poetry